The Evolving Impact of COVID-19 on Medical Student Orthopedic Education: Perspectives From Medical Students in Different Phases of the Curriculum. (28th September 2020) - Richardson, Michelle A.; Islam, Wasif; Magruder, Matthew
Introduction: The world-wide lockdown caused by Coronavirus Disease 2019 (COVID-19) has upended the trajectories of lives everywhere. The medical profession has been on the front lines of this rapidly developing situation, which in turn has called for unprecedented changes in the medical school curriculum. These changes have severe implications for medical students interested in applying to competitive surgical specialties like orthopedics. Methods: As medical students in 3 different class years pursuing orthopedic surgery, we provide our perspectives on the impact that COVID-19 has had on medical student orthopedic education. Results: With the removal of away rotations and a shift to virtual interviews, rising fourth year medical students are arguably the most impacted as they prepare for the orthopedic residency application process. Third year students, who are in the exploratory phase of choosing a specialty, also face uncertainties in the shift to a "new" clerkship experience that may (1) be of shorter duration, (2) implement shifts to limit overcrowding of clinical space, and (3) increase the use of telehealth over direct patient contact. Discussion: The COVID-19 pandemic has altered the course of medical students' orthopedic education in unprecedented ways. We believe the following suggestions may be helpful for students seeking alternative, supplemental ways of learning: (1) read up on major orthopedic journals, (2) reach out to orthopedic surgeons in areas of interest, (3) reach out to program directors/medical clerkship directors/program coordinators for opportunities to attend their educational curriculum virtually, (4) attend online lectures and hospital grand rounds, and (5) practice suturing technique with a practice kit. Conclusions: While the medical education landscape remains uncertain amid the evolving conditions of COVID-19, as medical students we strive to learn from this pandemic and respond to future unforeseen challenges with resilience, dedication, and compassion: all qualities we admire in orthopedic surgeons.